Complex method of the prognosis of tick-born neuroinfections - A. V. Subbotin; V. A. Semyonov; I. Yu. Torshin; O. A. Gromova; Ye. V. Fyodorova; N. N. Bashev (Бюллетень сибирской медицины)
Here, we propose a method of forecasting the development of the heavy forms of the tick-borne encephalitis using diagnostic tables. The method is based on evaluation of the patients with syndrome of endogenous intoxication using immunological and biochemical data along with evaluation of the clinical manifestations. We also propose an advanced form of the method that includes data based on the genotype of OAS1 — the gene, coding oligonucleotidesynthetase needed for immune response to RNA viruses. OAS1 genotype is an important risk factor since the differences in catalytic activity of OAS1 isoenzymes result in different susceptibility to the virus of the tick-borne encephalitis.